Investigación en enseñanza de las ciencias en la Universidad de Cornell: esquemas teóricos, cuestiones centrales y abordes metodológicos - Moreira, Marco Antonio; Novak, J. D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper provides a description of the kinds of telling questions, guiding theories, and research methodologies involved in the science education program at Cornell University in recent years, and that will continue to be in the research agenda in the near future. Given its research bias, it does not focus directly on matters such as curriculum development, instructional practices, and teacher preparation —which are also being carried out at Cornell —but rather on implications of research findings on these matters. By doing this, the authors attempt to be coherent with the fact that the program is theory -based and that in its development there has been a continuous effort to design both research and new instructional practices from a theoretical foundation, and in turn construct, modify, and elaborate the theoretical frameworks. An English version of this paper is available from the authors upon request.